Digital Ergonomics Analysis on the Productivity of Hybrid Workers in the Contemporary Indonesian Creative Industry - Dominica Maria Ratna Tungga Dewa (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The rapid growth of digital transformation and hybrid working systems has significantly changed work patterns in the contemporary Indonesian creative industry. Hybrid workers rely heavily on digital technologies, which create both opportunities for flexibility and challenges related to physical discomfort, cognitive overload, and communication fatigue. This study aims to analyze the influence of digital ergonomics on the productivity of hybrid workers in the Indonesian creative industry. The research employed a qualitative descriptive approach using the Narrative Literature Review (NLR) method. Data were collected from scientific journals, conference proceedings, books, and institutional reports published between 2016 and 2025 through databases such as Google Scholar, Scopus, and ScienceDirect. The analysis focused on physical ergonomics, cognitive ergonomics, communication ergonomics, and employee well-being in hybrid work systems. The findings indicate that digital ergonomics significantly affects worker productivity, creativity, psychological well-being, and work sustainability. Proper ergonomic work environments, balanced digital communication, effective workload management, and organizational support improve employee comfort, reduce fatigue and burnout, and enhance collaborative productivity within hybrid working environments in the Indonesian creative industry.